Right sided posterior diaphragmatic hernia with liver incarceration: A case report - Boitsios Alexi; Lacroix Sacha; Jehaes François; Monami Benoit (Clinical Case Reports, 2024)
Key clinical Message Right sided posterior diaphragmatic hernias are a rare diagnosis, especially in adult populations. This patient presented with right thoracic pain for 20 years before investigation. Imaging has provided an accurate diagnosis in this case. Repair can be done safely laparoscopically.